Amir’s Eyes Adventure Learning Amblyopia AR Storybook - Ahmad Azahar, Nur Azreene Suraya; Norizan, Azir Rezha (Journal of Computing Technologies and Creative Content, 2025)
“Amblyopia, or ‘lazy eye,’ is a common vision problem in children. If not treated early, it can lead to permanent vision issues. However, the current educational methods such as printed books and standard medical explanations may not effectively capture children’s attention or encourage interactive learning. There is a need for an engaging, interactive, and immersive learning tool that makes understanding amblyopia fun and accessible for children. Therefore, the main objective of this research is to develop an augmented reality (AR) storybook that educates children about amblyopia, causes, symptoms, and treatments through an engaging and interactive experience. This research uses the ADDIE model for designing and developing the AR storybook. The prototype was tested with 30 children, selected using purposive sampling. Data will be collected through user experience testing and feedback surveys. Based on this research, it is expected that this project will have a better understanding of amblyopia in a more engaging and interactive way, which could improve early diagnosis and treatment adherence. Based on the results, it will be proven that AR technology can enhance children’s learning experiences about amblyopia and make health education more accessible and effective.